Effect of platelet-rich and platelet-poor plasma on peri-implant innervation in dog mandibles - Dandan Song; Yan Huang; Jeroen Van Dessel; Sohaib Shujaat; Kaan Orhan; Tim Vangansewinkel; Kathleen Van den Eynde; Ivo Lambrichts; Tania Roskams; Constantinus Politis; Reinhilde Jacobs (SpringerOpen, 2019)
Abstract Background Autologous plasma fractions, such as platelet-rich plasma (PRP) and platelet-poor plasma (PPP), contain growth factors that can enhance neural cell survival and are therefore likely to have the ability to promote nerve regeneration. The present study compared the effect of PRP and PPP application on myelinated nerve density and diameter in the peri-implant bone region. In addition, the effect of healing time on nerve regeneration was assessed. Materials and methods Nine beagle dogs randomly received 54 dental implants in the bilateral mandible according to a split-mouth design. Each implant was randomly assigned to one of three implant protocols: delayed implant placement with delayed loading (DIP + DL) with local application of PRP, DIP + DL with local application of PPP and DIP + DL without any plasma additive. The animals were euthanized at 1, 3, and 6 months after loading (3 dogs per time point). Block biopsies were prepared for histomorphometry in the peri-implant bone within 500 μm around the implants. Results Myelinated nerve fibers were identified in the trabecular bone and in the osteons near the implants surface. The nerve fibers in the PRP group (median ± IQR; 2.88 ± 1.55 μm) had a significantly (p < 0.05) greater diameter compared to the PPP (2.40 ± 0.91 μm) and control (2.11 ± 1.16 μm) group. The nerve diameter after 6 months healing (3.18 ± 1.58 μm) was significantly (p < 0.05) greater compared to 1 (2.08 ± 0.89 μm) and 3 (2.49 ± 1.22 μm) months. No significant difference was found for myelinated nerve density between groups and healing time. Conclusions The present study showed that the healing time significantly influenced the diameter of the myelinated nerve fibers in peri-implant bone. PRP exerted a significant effect on the diameter of the myelinated nerve fibers as compared to PPP. Large-scale animal studies and longer follow-up periods are needed to confirm these findings and to verify whether platelet plasma can facilitate nerve regeneration process.